ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DALAM MELAKUKAN PEMBELIAN PADA SALWA HOUSE KAFE - Nofita, Erika Dian; Kamal, Mustafa (Faculty of Economics and Business Diponegoro University, 2013)
This study aims to determine how big the influence price perception, product quality, and service quality of the consumer satisfaction on SalwaÂ House. And this research also aims toanalyze the most dominant factors that influence on consumer satisfaction of Salwa House.The population used in this study is consumers of Salwa House. The sample in this study are 100 respondents and the technique used is non-probability sampling technique with the approach of purposive sampling.From the analysis result, the indicators in this study are valid and reliables. The most dominant factor that influence on consumer satisfaction are service quality, then the product quality, and the last is price perception. Then though the F Test can be seen that the independent variables feasible to test the dependent variable. The result of Adjusted R Square is 0,640, it means that independent variable can explain about 64% of dependent variable